BIOPROCESSES DEVELOPMENT FOR REDUCING LEVELS OF EFFLUENT BOD AND COD FOOD INDUSTRY - Flores P., Abad (2008)
It was developed a biotechnological process to reduce chemical oxygen demand (COD) & Biochemical Oxygen Demand (BOD) from industrial waste water, simultaneously, it was evaluated the potential bioconversion of some yeast into Food yeast & ethanol production. It was produced a reduction of the Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) of potatoes starchy processing industry from 22,5000 Chemical Oxygen Demand (COD) and Biochemical Oxygen demand (BOD) of COD to 1480 mg O2/ L and 26,400 mg O2/L BOD to 2100 mg O2/ L BOD with an aerobic mixed culture of Candida tropicalis BT-UNSM 124 and LIpomyces sp BT-UNMSM-145. It was produced a reduction of Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (DBO) of dairy effluent diluted from 22,100 mg O2/ L COD to 1280 mg O2/ L and 17,500 mg O2 / L BOD to 1100 mg O2/ L of BOD with an aerobic culture of Kluyveromyces marxianus NRRL-Y-1109 and a reduction of COD from 22,100 mg O2/ L to 1360 mg de 02/ L and reduction of BOD from 17,600 mg O2/ L to 1259 mg O2/ L with an aerobic culture of Candida pseudotropicalis.